Differential Diagnosis of Taenia saginata and Taenia solium Infection by PCR - González, Luis Miguel (American Society for Microbiology, 2000)
We have designed species-specific oligonucleotides which permit the differential detection of two species of cestodes, Taenia saginata and Taenia solium. The oligonucleotides contain sequences established for two previously reported, noncoding DNA fragments cloned from a genomic library of T. saginata. The first, which is T. saginata specific (fragment HDP1), is a repetitive sequence with a 53-bp monomeric unit repeated 24 times in direct tandem along the 1,272-bp fragment. From this sequence the two oligonucleotides that were selected (oligonucleotides PTs4F1 and PTs4R1) specifically amplified genomic DNA (gDNA) from T. saginata but not T. solium or other related cestodes and had a sensitivity down to 10 pg of T. saginata gDNA. The second DNA fragment (fragment HDP2; 3,954 bp) hybridized to both T. saginata and T. solium DNAs and was not a repetitive sequence. Three oligonucleotides (oligonucleotides PTs7S35F1, PTs7S35F2, and PTs7S35R1) designed from the sequence of HDP2 allowed the differential amplification of gDNAs from T. saginata, T. solium, and Echinococcus granulosus in a multiplex PCR, which exhibits a sensitivity of 10 pg.